2017
DOI: 10.1038/s41598-017-00107-w
|View full text |Cite
|
Sign up to set email alerts
|

Amplification on Undirected Population Structures: Comets Beat Stars

Abstract: The fixation probability is the probability that a new mutant introduced in a homogeneous population eventually takes over the entire population. The fixation probability is a fundamental quantity of natural selection, and known to depend on the population structure. Amplifiers of natural selection are population structures which increase the fixation probability of advantageous mutants, as compared to the baseline case of well-mixed populations. In this work we focus on symmetric population structures represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 35 publications
2
53
1
1
Order By: Relevance
“…Of course, stronger amplifiers of selection are already known 1 , but they are all directed or weighted graphs. Pavlogiannis et al found a class of undirected graphs that they call comets which can have a higher fixation probability than stars for certain graph sizes of more than 100 nodes 33 . Comet-graphs consist of a complete graph with a star attached to one of the nodes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of course, stronger amplifiers of selection are already known 1 , but they are all directed or weighted graphs. Pavlogiannis et al found a class of undirected graphs that they call comets which can have a higher fixation probability than stars for certain graph sizes of more than 100 nodes 33 . Comet-graphs consist of a complete graph with a star attached to one of the nodes.…”
Section: Resultsmentioning
confidence: 99%
“…With the fast computational method we use for computing fixation probability and time, we are limited to sizes roughly up to N = 23 31 . There are many interesting findings for larger graphs, e.g., that the star is not the strongest amplifier for all sizes, but that comets can have an even higher fixation probability 33 . Our genetic algorithm can be easily combined with other methods of computation or simulation to tackle larger graph sizes.…”
Section: Discussionmentioning
confidence: 99%
“…To design a vaccine construct, the elected B and T cells epitopes were fused using appropriate specialized spacer (linkers) sequences in order to generate multi-epitopes peptides [ 44 ]. The linkers KK and GPGPG were introduced between the selected B and T cells epitopes to generate a sequence with minimal junctional immunogenicity [ 45 – 49 ]. The EAAAK linker was also added between the adjuvants sequences and the fused epitopes in order to reach a high level of expression and improved bioactivity of the fused epitopes [ 44 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The star graph is known to have the strongest amplification among undirected graphs up to now. (Recently, in a limited interval for r, a family of graphs (comets) with higher fixation probability than the star graphs is discovered [7]. )…”
Section: Introductionmentioning
confidence: 99%